SEISMIC REGIME OF THE ZHONGARO-BALKHASH REGION ACCORDING TO INSTRUMENTAL DATA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The results of studying the seismic regime of weak earthquakes in the Zhongar-Balkhash region for the period of instrumental observations for 1951-2022 are carried out. The zoning of the territory was carried out according to the magnitude of seismic activity and the depth of occurrence of earthquake sources. The most seismically active zone, confined to the South Zhongaria, has been identified. The results of the work are used in assessing the seismic hazard of the territory.
Keywords: Zhongar-Borohoro region; seismicity; seismic regime; seismically active zones; earthquake sources; seismic hazard